The formation and development of meat cluster in West Kazakhstan region - Kazambayeva А.М.; Sultanova, Z.Kh. (BUKETOV BUSINESS REVIEW, 2019)
One of the key factors for the effective development of meat production is the rational use of existing production resources, natural and climatic conditions and organizational and economic factors of the region. The purpose of the study was the theoretical and methodological substantiation of the optimal conditions for the creation of meat cluster in West Kazakhstan region. For assessment of possibility of meat cluster creation, the analysis of the functioning livestock industry in the region and the peculiarities of organizational influence and economic mechanism of interrelations of the meat cluster participants was conducted. It has been established that West Kazakhstan region is bordered by 5 regions of Russian Federation, which allows to export meat products. So in 2017, the export of beef amounted to 1736,5 tons. One of the problems in the development of the industry is the insufficient workload of meat processing enterprises due to insufficient load of raw materials, the unfinished mechanism of relations between meat processing plants and agricultural producers. Therefore, the creation of meat cluster in the regions allows to effectively attract government stimulation of business and science to the cattle meat production, and due to technological modernization and the implementation of scientific research results, it is possible to reach steady positive dynamics of animal growth. The complex methods of research are used: the abstract, the study of dynamic trends. These methods of research allow to make logical analysis of the collected facts, to develop concepts and judgments, to make conclusions and theoretical generalizations.